Sports medicine leaders working with government and public health to plan a `return-to-sport` during the COVID-19 pandemic: the UK`s collaborative five-stage model for elite sport - Kemp, S.; Cowie, C. M.; Gillett, M.; Higgins, R.; Hill, J.; Iqbal, Z.; Jackson, P.; Jaques, R.; Larkin, J.; Phillips, G.; Peirce, N.; Calder, J. (British Journal of Sports Medicine, 2021)
The chief medical officers of many of the major Olympic, Paralympic and Professional Sports in the UK formed a group to share thinking around how elite sport might best plan for a return at the appropriate time. While it was acknowledged that there were fundamental differences between the sports, including but not limited to current and future competition schedules, financial and personnel resources, potential risks of COVID-19 transmission between participants and their ability to align with any relaxation of population social distancing (SD), a collaborative approach to planning `how` elite sport might restart was agreed to be the most effective manner to inform a single dialogue with government and Public Health England.